Haram Statement on Digital Wallet Discounts; A Critical Approach - Widyarini, Widyarini; Avisha, Lady (UIN Mataram, 2024)
Smartphone and tech-savvy users, have a tendency to choose digital wallets instead of physical wallets. In addition to being practical, digital wallets offer many advantages such as: discounts, free shipping, cashback, so that users can shop more efficiently. The MUI fatwa on the use of the digital wallet discount law does not yet exist, so various opinions have emerged on its halal law. This research is a qualitative library research, with the aim of revealing about the halalness of digital wallets and the provision of discounts on digital wallets, so that users do not hesitate in using digital wallets. The results showed that the law of digital wallet discounts is halal, so the haram statement of the digital wallet discount law is not true. The contract on a digital wallet is wadiah yad dAmanah contract, not a qard contract. Discounts on digital wallets are in accordance with the provisions of Islamic law and are in line with maqa>sid shari>’ah. Discounts on digital wallets are not a benefit of qard but 'ata>ya.